2, 3-Dimethylpyrazine (3DP) and 2, 5-dimethyl-4-hydroxy-3(2H)-furanone (DMHF) generated by the Maillard reaction in foods affect autonomic nervous activity and central nervous activity in human. Issue 9 (1st September 2020) - Ohata, Motoko; Zhou, Lanxi; Yada, Yukihiro; Yokoyama, Issei; Arihara, Keizo
ABSTRACT: This study investigated the effect of the odors generated by the glycine/glucose Maillard reaction and the potent odorants 2, 3-dimethylpyrazine (3DP) and 2, 5-dimethyl-4-hydroxy-3(2 H )-furanone (DMHF) on the human mood and integrative physiological activity. The score of certain subjective moods, especially anger-hostility, and tension-anxiety were decreased significantly after inhalation of the Maillard reaction sample and DMHF, and fatigue-inertia mood was also significantly decreased by DMHF, suggesting a sedative effect of these odors on mood, while 3DP had no effect. Miosis rate and fingertip temperature increased significantly following inhalation of the odor from the Maillard reaction sample and both potent odorants, suggesting that the parasympathetic nervous system dominates through suppression of the sympathetic activity. The physiological relaxing effect of these odors was also confirmed by decreased flicker frequency value and decreased oxyhemoglobin in the prefrontal cortex. Graphical Abstract: Inhalation of 3DP or DMHF induced parasympathetic dominance by suppression of sympathetic nervous system and led to a decrease in oxyhemoglobin in the prefrontal cortex.